Are authentic tourists happier? Examining structural relationships amongst perceived cultural distance, existential authenticity, and wellbeing. (15th August 2019) - Yu, Jibin; Li, Hanliang; Xiao, Honggen
Abstract: The existential authenticity theory and eudaimonism theory imply that perceived cultural distance facilitates existential authenticity, which then conduces to hedonic and eudaimonic wellbeing. This study examined these presumptions basing on quantitative data collected through questionnaire survey in China. Results suggest that perceived cultural distance is not related to existential authenticity, and existential authenticity is positively related to hedonic and eudaimonic wellbeing. Hence, physically breaking away from one's home culture does not guarantee existential authenticity, and experiencing greater existential authenticity is related to correspondingly greater hedonic and eudaimonic wellbeing. Theoretical and practical implications of this research are also discussed.